AR 2017
DOI: 10.21873/anticanres.12020
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Status of Primary Colorectal Cancer Predicts the Incidence of Postoperative Colorectal Neoplasms

Abstract: The MS status of primary colorectal cancer influenced the risk of postoperative colorectal neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…According to the GLOBOCAN project of the WHO Cancer Research Center, the number of new cases of CRC in 2018 was about 1.8 million, and the number of deaths was about 880,000. The incidence of CRC is related to factors such as age, region, and gender ( Takiyama et al, 2017 ; Zhou et al, 2022 ). The pathological types of CRC are divided into ulcerative, raised, and infiltrating.…”
Section: Discussionmentioning
confidence: 99%
“…According to the GLOBOCAN project of the WHO Cancer Research Center, the number of new cases of CRC in 2018 was about 1.8 million, and the number of deaths was about 880,000. The incidence of CRC is related to factors such as age, region, and gender ( Takiyama et al, 2017 ; Zhou et al, 2022 ). The pathological types of CRC are divided into ulcerative, raised, and infiltrating.…”
Section: Discussionmentioning
confidence: 99%
“…of microsatellite markers as BAT25, BAT26, D2S123, D5S346, and D17S2720; the amplification of BAT26 (100%); and the reduction of D17S2720 (85.4%), confirming its use as a prognostic marker in colorectal carcinogenesis. Other studies investigating MSI status showed a high association among microsatellite loci, BAT25 and BAT26, and the more aggressive histopathological types (tubulovillous/villous adenoma) of SCRC [18].…”
mentioning
confidence: 87%
“…Some papers present the MSI as a marker of a significant prognostic factor in the early SCRC stages [3,15,18]. Zhang & collaborators [19] showed that the MS-I status was found to be significantly correlated with good or moderate histopathological differentiation associated with low carcinoembryonic antigens and CA-19-9 antigen values.…”
Section: Microsatellite Instability (Msi)mentioning
confidence: 99%